Verbal Abuse on Pre-School Children: The Case of Indonesian Children - Andriyani Mustika Nurwijayanti; Muhammad Khabib Burhanuddin Iqomh (GLOBAL HEALTH SCIENCE GROUP, 2019)
Verbal abuse is a form of violence received by children in the form of words that hurt the children. The impact of verbal abuse on children causes them to behave aggressively, emotional disturbances, and personality disorders. To explore this phenomenon, this research was designed employing descriptive approach. 132 children (henceforth, respondents)were randomly recruited. The age of respondents ranged from 32 to 34 years.The majority of were high school students with 116 (87.9%) in number, while otehrs were housewives, 113 respondents (85%) in number. Data in this study were collected through questionnaire. The data were then analyzed descriptively.The results of this showed that light verbal abuse were received by 15 respondents (11.4%) and heavy verbal abuse by 117 respondents (88.6%).   Keywords: verbal abuse, pre-school children, parents